Purification, crystallization and preliminary X-ray crystallographic analysis of chitinase from Bacillus cereus NCTU2 - Kuo, Chueh-Yuan (International Union of Crystallography, 2006)
Chitinases (EC 3.2.1.14) are found in a broad range of organisms, including bacteria, fungi and higher plants, and play different roles depending on their origin. A chitinase from Bacillus cereus NCTU2 (ChiNCTU2) capable of hydrolyzing chitin as a carbon and nitrogen nutrient has been identified as a member of the family 18 glycoside hydrolases. ChiNCTU2 of molecular weight 36 kDa has been crystallized using the hanging-drop vapour-diffusion method. According to the diffraction of chitinase crystals at 1.10 Å resolution, the crystal belongs to space group P2(1), with unit-cell parameters a = 50.79, b = 48.79, c = 66.87 Å, β = 99.31°. Preliminary analysis indicates there is one chitinase molecule in the asymmetric unit, with a solvent content of 43.4%.